The Effect of Budget Participation to Budgetary Slack With External Pressure as Moderating Variable - Rifqi, Robith Abdullah; Subekti, Imam; Rahman, Aulia Fuad (Journal of Accounting and Business Education, 2017)
This study aims to examine empirically the effect of budget participation on budgetary slack and the influence of external pressure as a moderating of the relationship between budget participation and budgetary slack in Probolinggo Municipal Government. The sample was 105 employees participated in the budgeting process at 40 Local Government Units (LGU) in Probolinggo Municipal Government. This study was using multiple linear regression. The outcomes indicated that the greater level of employee participation in the preparation of the budget, the budgetary slack will be reduced. Unfortunately, this study was not able to prove that the interaction between budget participation and external pressure strengthen the relationship between budget participation and budgetary slack. Yet, external pressure can reduce budgetary slack.Keywords: budget participation, budgetary slack, external pressure.